Difference In Knowledge Between Primigravida And Multigravida Mothers About The Danger Signs Of Pregnancy At Seririt 1 Health Center - Wardana, Ketut Eka Larasati; Triguno, Yopita; Wulandari, Ni Ketut Ayu (Chakra Brahmanda Lentera Institute, 2021)
Background: Maternal Mortality Rate (AKI) is one of the efforts to assess the degree of public health. One of the problems associated with maternal mortality is pregnancy problems that should be avoided. Pregnancy problems can be detected early from the presence of danger signs in pregnancy. One of the factors that influences mothers knowing the danger signs of pregnancy is the mother's knowledge. From the preliminary study conducted there is still a difference in knowledge between primigravida and multigravida mothers about the danger signs of pregnancy in Seririt I Health Center. The purpose is to find out the difference in knowledge between primigravida and multigravida mothers about the danger signs of pregnancy in Seririt I Health Center..Methods: Research methods is Comparative Study with a cross sectional approach. The population is primigravida and multigravida pregnant women in Seririt I Health Center in 2021, with purposive sampling and obtained a sample of 52 respondents. The research instrument used is a questionnaire. The results of the study were then analyzed with an independent T-test.Results: The results of the analysis showed no difference in knowledge between primigravid mothers and multigravidas about pregnancy danger signs in Seririt 1 Health Center with a p-value of 0.000 and p-value of 0.0160 so that p-value>α 0.05.Conclusion: Conclusion there is no difference in knowledge between primigravida and multigravid mothers about the danger signs of pregnancy.